Interpreting Women's Emancipation in the Context of Islamic Multiperspectivism: An Analytical Approach - Widiyanti, Dewi; Firdaus, Muammar (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2023)
This study aims to investigate, analyze, and establish a model for the study of women's emancipation from an Islamic perspective. The research methodology employs a qualitative interpretive paradigm, utilizing literature-based techniques. Data for the research was sourced from 50 different materials, including books, research findings, and digital news. The data search incorporated keywords such as women's emancipation, gender, and Islamic views. The results indicate that emancipation studies are conducted through a multi-perspective approach encompassing historical perspectives, Islamic law perspectives, and Al-Qur'an perspectives. From these three perspectives, it is evident that Islam has elevated the status of women, leading to equality between women and men. This study implies a shift in societal paradigms, recognizing that women deserve opportunities to contribute in all aspects of society. Such functionalization is implemented with consideration for religious norms, social conditions, and individual competencies. AbstrakPenelitian ini bertujuan untuk menyelidiki, menganalisis, dan membangun model studi emansipasi wanita dari perspektif Islam. Metodologi penelitian ini menggunakan paradigma interpretatif kualitatif, dengan menggunakan teknik-teknik berbasis literatur. Data untuk penelitian ini bersumber dari 50 bahan yang berbeda, termasuk buku, temuan penelitian, dan berita digital. Pencarian data menggunakan kata kunci seperti emansipasi wanita, gender, dan pandangan Islam. Hasil penelitian menunjukkan bahwa studi emansipasi dilakukan melalui pendekatan multi-perspektif yang mencakup perspektif sejarah, perspektif hukum Islam, dan perspektif Al-Qur'an. Dari ketiga perspektif tersebut, terbukti bahwa Islam telah mengangkat derajat perempuan, yang mengarah pada kesetaraan antara perempuan dan laki-laki. Penelitian ini mengimplikasikan adanya pergeseran paradigma masyarakat yang mengakui bahwa perempuan berhak mendapatkan kesempatan untuk berkontribusi dalam segala aspek kehidupan. Fungsionalisasi tersebut diimplementasikan dengan mempertimbangkan norma-norma agama, kondisi sosial, dan kompetensi individu.